1996
DOI: 10.1136/thx.51.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatotoxicity from antituberculosis drugs: a case-control study.

Abstract: Background -Several risk factors for the development of hepatotoxicity during short course antituberculosis therapy have been suggested. A case-control study was undertaken to assess the role of age, sex, disease extent, nutritional status, past history of liver disease, infection with hepatitis viruses, acetylator status, and high alcohol intake as risk factors in the development of hepatotoxicity in patients with pulmonary tuberculosis receiving antituberculosis treatment. Methods -The cases comprised 86 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
140
8
9

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 18 publications
14
140
8
9
Order By: Relevance
“…Similar conclusions were made in two other reports. 17,18 Patients infected with hepatitis B and hepatitis C (n ¼ 14) had no recorded increases in ALT value. However, the numbers are too small to allow any comment on safety.…”
Section: Discussionmentioning
confidence: 97%
“…Similar conclusions were made in two other reports. 17,18 Patients infected with hepatitis B and hepatitis C (n ¼ 14) had no recorded increases in ALT value. However, the numbers are too small to allow any comment on safety.…”
Section: Discussionmentioning
confidence: 97%
“…In literature, there is a wide disparity in the reported incidence of ATT-induced hepatitis ranging from 2 to 39% [2,5]. The incidence has been reported to be higher in developing countries and factors such as acute or chronic liver disease, indiscriminate use of drugs, malnutrition and more advanced tuberculosis have been implicated [13,14]. The reported mortality from ATT-induced hepatitis after the development of jaundice varies from 4-12% [15].…”
Section: Discussionmentioning
confidence: 99%
“…While some papers have focused on genetic factors, such as HLA typing [8], Cytochrome P450 2E1 20 or acetylator status, [13] others have primarily studied clinical factors, as the present study. Some studies have reported that the risk of ATTinduced hepatitis increases with advancing age, the highest incidence being in individuals older than 50 years [14].…”
Section: Discussionmentioning
confidence: 99%
“…7 The incidence of INH-induced hepatotoxicity ranges from 1 to 36%, depending on different regimens, the population being treated and the definition of hepatic injury used. 8,9 Alcohol consumption, presence of HIV, advanced age and chronic liver disease have been reported to increase the risk of INH-induced hepatotoxicity. [10][11][12][13][14] N-acetyltransferase 2 (NAT2) is directly involved in INH metabolism, and genetic variation in the NAT2 gene has been reported to be a risk factor for INHinduced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%